Efek Curing Time Komposit Serat Karbon Pada Filler Hollow Glass Microsphere (HGM) 10 % Menggunakan Metode RSM - Yuliyanto, Yuliyanto; Zulfitriyanto, Zulfitriyanto; Subarkah, Imam (Manutech : Jurnal Teknologi Manufaktur, 2024)
Composite is a type of material or new material made from engineering, consisting of two or more materials, composed of fiber as reinforcement and matrix as adhesive or fiber binder. Carbon fiber is a synthetic fiber that has a very thin size of around 0.1 mm which is very strong and light. This research aims to determine the effect of curing time and other parameters on the flexural strength of carbon fiber composites with Hollow Glass Microsphere (HGM) Filler. Data analysis uses Response Surface Methodology (RSM). The highest average bending test results were found in test 1 with parameters of fiber percentage of 30%, fiber length of 100 mm and curing time of 6 hours of 212 MPa. The lowest average test was in the 20th test, with parameters of fiber percentage of 10%, fiber length of 100 mm and curing time of 6 hours of 72.5 MPa. An increase in the curing time value will result in a decrease in flexural strength. Because the longer the caring time takes, the harder and more brittle the carbon fiber becomes. Another effect is that the fibers experience shrinkage and become smaller so that they form voids or small holes between the fibers and the matrix. A higher percentage of fiber influences the resulting bending strength to be stronger. Because the forces that resist during the testing process are more numerous andlarge. The effect of fiber length on flexural strength does not have a significant effect.